Green Infrastructure and Social Justice: An Evaluation of the Makassar–Barru Railway Development from the Perspective of the SDGs - Suriyani (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2025)
The construction of the Makassar–Barru railway line is one of Indonesia’s national strategic projects designed to strengthen interregional connectivity and accelerate economic growth. However, behind these objectives lie significant social, economic, and ecological dynamics for rural communities in Barru Regency. This study aims to evaluate the development of the Makassar–Barru railway line from the perspective of green infrastructure and social justice within the framework of the Sustainable Development Goals (SDGs). Using a qualitative approach with a rural sociology perspective, data were collected through in-depth interviews, field observations, and policy document analysis. The findings indicate that the implementation of green infrastructure principles remains limited to technical aspects and has not fully addressed social and ecological dimensions. Inequality in the distribution of development benefits and weak community participation show that social justice has not been fully realized. Nevertheless, local initiatives highlight the adaptive capacity of communities in responding to change. This study underscores the importance of an inclusive, participatory, and sustainable infrastructure development model aligned with the SDGs agenda to promote social justice and environmental sustainability in rural areas.